Simultaneous Adsorption and Degradation of Cr(VI) and Cd(II) Ions from Aqueous Solution by Silica-Coated Fe0 Nanoparticles. (15th December 2013) - Li, Yongchao; Ma, Hongpu; Ren, Bozhi; Li, Tielong
Abstract : Core-shell silica-coated Fe 0 nanoparticles (Fe@SiO2 ) were prepared in one-step synthesis by aqueous reduction combined with modified Stöber method. The as-prepared Fe@SiO2 were then used for simultaneous removal of Cr(VI) and Cd(II) from aqueous solution. Batch tests indicated that Fe@SiO2 exhibited high removal capacity toward Cr(VI) and Cd(II). Cr(VI) was removed by Fe@SiO2 through reduction rather than adsorption, while Cd(II) removal was mainly through adsorption. The removal rate increased with increasing initial Fe NPs dose and decreased with increasing initial Cr(VI) and Cd(II) concentrations. Cd(II) adsorption was also strengthened by Cr(VI) reduction with the release of OH − . The removals of Cr(VI) and Cd(II) were weakened in the presence of cations or humic acid, as a result of aggregation and less active site of Fe@SiO2 . Overall, the simply prepared Fe@SiO2 were potential material for the heavy metals removed from water.